Effectiveness of in-service training program to develop the professional performance of teachers in the special education complex / Al-Quds Open University - Suhail, Tamer Farah (Dirasat: Educational Sciences, 2020)
This study aims to identify the effectiveness of a training program to develop the professional performance of trainee teachers in the special education complex (Al-Quds University). The study also investigated the effect of teacher gender, educational qualification, and years of teaching experience on trainee teachers’ perceptions of the effectiveness of the training program. The study used the quasi-experimental method to evaluate the effectiveness of the training program. A purposefully selected sample of (35) trainee teachers (11 males and 24 females) from the special education complex at Al-Quds University participated in the study. The researcher used a 34 - item scale to measure the effect of the training program after establishing its validity and reliability. The scale consisted of the following six domains: personal skills, measurement and diagnosis skills, individualized education plan development, instructional plan implementation, communicating with parents, and using technology in teaching. The study results showed that there were statistically significant differences (α = 0.05) between the pretest (before training) and posttest (after training) favoring the latter. The results indicated that there were no differences due to the effect of sex, scientific qualification, or years of teaching experience. The findings of the current study provides evidence of the effectiveness of the training program in helping teachers of students with special needs improve their professional performance.